2000
DOI: 10.1007/bf03179903
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin and cyclosporine modulate adenosine transporters and adenosine A1 receptors in the rat brain

Abstract: The existence of adenosine A1 receptors and adenosine transporters in the central nervous system has been well demonstrated, although their possible modulation by hormones and/or exogenous drugs is poorly understood. To further analyze these modulatory mechanisms, the effects of prolactin and cyclosporine (CyA) on adenosine A1 receptors and transporters were analyzed in the central nervous system. For this purpose the number and affinity of adenosine A1 receptors were measured using the specific antagonist 1,3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Previous studies showed that CsA and FK506 produce an increase in ADO levels by inhibition of the enzyme AK associated to the plasma membrane, in different cell types [10,11]. Moreover, an inhibition of cell uptake of the nucleoside has been described, and CsA has been shown to reduce by 67% the number of ADO transmembrane transporters in rat brain [20]. The mechanisms are closely related, as it has been demonstrated that it is unlikely that AK blocking may take place without the inhibition of cell uptake of ADO [33,34].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previous studies showed that CsA and FK506 produce an increase in ADO levels by inhibition of the enzyme AK associated to the plasma membrane, in different cell types [10,11]. Moreover, an inhibition of cell uptake of the nucleoside has been described, and CsA has been shown to reduce by 67% the number of ADO transmembrane transporters in rat brain [20]. The mechanisms are closely related, as it has been demonstrated that it is unlikely that AK blocking may take place without the inhibition of cell uptake of ADO [33,34].…”
Section: Discussionsupporting
confidence: 88%
“…As a consequence, AK‐mediated ADO dephosphorylation to adenosine monophosphate (AMP) is inhibited, and cell release of ADO is promoted [9–11]. Moreover, an inhibition of ADO cell uptake has also been reported, and CsA has been described to reduce by 67% the number of ADO transporters in the rat brain [20]. The activity of CsA and FK506 on the ADO system was studied in vitro in red blood cells [9], endothelial cells [10] and T lymphocytes [11].…”
Section: Introductionmentioning
confidence: 99%